The possessed : adventures with Russian books and the people who read them - Batuman, Elif, 1977- (Farrar, Straus and Giroux, 2010)
Literally and metaphorically following the footsteps of her favorite authors, Batuman searches for the answers to the big questions in the details of lived experience, combining fresh readings of the great Russians, from Pushkin to Platonov, with the sad and funny stories of the lives they continue to influence--including her own.